Managing Uncertainty from Planning and Design to Construction Process of Building Refurbishment Projects: A Proposed Conceptual Approach - Yacob, Ridzuan; Saruwono, Masran; Ismail, Zulhabri (International Journal of Sustainable Construction Engineering and Technology, 2019)
The number of building refurbishment projects in Malaysia has increased significantly over the past few years. Empirical data from previous research confirmed that managing Building Refurbishment Project (BRP) is demanding and risky which is inherent in Uncertainty Factor (UF) associated with unforeseen elements, mostly comprising of actual cost that exceeds budget. This occurs when they involve structural modifications with sensitive, dangerous, difficultoperations with large number of sub-contractors, and the high number of building services that has always been identifiedas one of the reasons for poor performance. The reasons were as stated because UF of construction process was less emphasised compared to planning and design process. This emphasis is however questionable in the real world as the UF is consistent throughout the BRP life cycle. This paper aims to determine the UF of construction process and the relationship with BRP performance.The method used for this study is based on a comprehensive review of related journal papers, book chapters and conference papers from 1997 to 2018, from which 125 articles were identified and 51 papers were subsequently selected for further analysis. This study concluded that UF of construction process is indeed one of the most important factors that influence the performance of BRP. On that basis, there is still room for improving the level of BRP performance. The findings of this study form the foundation for an extended investigation to identify UF specifically in the construction process to serve as a guide in managing the UF and improving BRP performance in Klang Valley.